2016
DOI: 10.1111/jdv.13831
|View full text |Cite
|
Sign up to set email alerts
|

Ingenol mebutate in actinic keratosis: a clinical, videodermoscopic and immunohistochemical study

Abstract: The clinical efficacy of ingenol mebutate on AKs is confirmed by its effect on angiogenesis, stem cell activity and cell proliferation in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 36 publications
3
26
0
2
Order By: Relevance
“…It directly stimulates B cells to produce specific antineoplastic antibodies, interacting both on dysplastic AK or NMSC cells and on neutrophils in the inflammatory infiltrate. 18 Anti-proliferative effects have been demonstrated also in a study by Bobyr et al, 29 showing a significant reduction in neoangiogenesis marker VEGF and proliferation marker Ki67 after treating AKs with ingenol mebutate, alongside reduction in expression of p63, which is reported by the authors a reliable marker of actinic damage. In addition, ingenol mebutate might act as potent agonist of protein kinase C delta, 25 leading to an anti-proliferative effect and a regulatory effect on immune cell activation.…”
Section: Discussionsupporting
confidence: 52%
“…It directly stimulates B cells to produce specific antineoplastic antibodies, interacting both on dysplastic AK or NMSC cells and on neutrophils in the inflammatory infiltrate. 18 Anti-proliferative effects have been demonstrated also in a study by Bobyr et al, 29 showing a significant reduction in neoangiogenesis marker VEGF and proliferation marker Ki67 after treating AKs with ingenol mebutate, alongside reduction in expression of p63, which is reported by the authors a reliable marker of actinic damage. In addition, ingenol mebutate might act as potent agonist of protein kinase C delta, 25 leading to an anti-proliferative effect and a regulatory effect on immune cell activation.…”
Section: Discussionsupporting
confidence: 52%
“…We found that treatment of AK with IM induced a significant clinical improvement rate of 80% in Korean patients with AK. Previous studies have reported a clinical clearance rate of AK lesions 2 months after treatment with IM within the range of 49% to 100%, but there is no existing data in the Asian population. Treatment with IM showed the favorable treatment outcomes when compared with many other therapies used in the treatment of AK including cryotherapy (39–83%), 3.0% diclofenac gel (33–50%), imiquimod 5% cream (45.1%) and 5‐fluorouracil 0.5% cream (19.5–47.5%.)…”
Section: Discussionmentioning
confidence: 98%
“…We observed a histopathological clearance rate of AK lesions of 66.7% after IM treatment in Koreans. Until now, only two studies have examined the histopathological improvement after treatment with IM . Bobyr et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations